2020
DOI: 10.1007/s00429-020-02148-w
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical changes associated with age-related hearing loss and listening effort

Abstract: Age-related hearing loss is associated with a decrease in hearing abilities for high frequencies and therefore leads to impairments in understanding speech—in particular, under adverse listening conditions. Growing evidence suggests that age-related hearing loss is related to various neural changes, for instance, affecting auditory and frontal brain regions. How the decreased auditory input and the increased listening effort in daily life are associated with structural changes is less clear, since previous evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 58 publications
(118 reference statements)
0
25
0
1
Order By: Relevance
“…However, this is mere speculation and the question remains open for further investigation. Complicating this issue, hearing loss has been associated with reduced gray matter volume in the primary auditory cortex 11 , 52 , among other brain volume changes 53 , 54 (although some studies found no effects, see 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is mere speculation and the question remains open for further investigation. Complicating this issue, hearing loss has been associated with reduced gray matter volume in the primary auditory cortex 11 , 52 , among other brain volume changes 53 , 54 (although some studies found no effects, see 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, human imaging data have shown structural and functional changes in this cortico-limbic and auditory brain circuitry following hearing impairment. Hearing loss has been shown to be associated with significantly lower grey matter volume in the PFC in individuals with hearing loss compared to normal-hearing individuals [ 25 , 26 ]. Increased functional coupling between the PFC and auditory cortex has been demonstrated in hearing impaired individuals compared to normal hearing controls [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have read the letter by Xiaoling Yin and Yun Zheng in critique to our research that was published as "Neuroanatomical changes associated with age-related hearing loss and listening effort" (Rosemann and Thiel 2020). We appreciate the concerns of the authors of this letter and hereby take the opportunity to respond to those comments.…”
Section: Dear Editormentioning
confidence: 99%